PERANCANGAN SISTEM INFORMASI DI PTAIS KOPERTAIS WILAYAH VII SUMATERA SELATAN - Fenny Purwani (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2014)
Relations and information technology today closely related. One technology that is widely used and very popular on the Internet is a website. The website is agood means to facilitate and share information as much to college. However, the college today togetthe informationisnot maximized. This study aimstobuildawebsite on Kopertais SUMBAGSEL region VII. This website was developed using Macromedia Dreamweaver CS3 software, PHP, and MySQL, and method development using RAD (Rapid Application Development), and the purpose of this website serves to facilitate the college to receiver elevant information about online Kopertais VII region and terupdates.